Squamous cell histological transformation in a lung adenocarcinoma patient (hyper) progressing upon immunotherapy. Issue 6 (December 2022) - Mariniello, Annapaola; Righi, Luisella; Morrone, Antonio; Carnio, Simona; Bironzo, Paolo
Introduction: In non-small cell lung cancer (NSCLC) histologic transformation upon immune checkpoint inhibitors (ICI) is rare. Case presentation: We described the case of a patient with early-stage lung adenocarcinoma who relapsed after surgery. At the time of relapse, he received chemo-radiotherapy, followed by consolidation immunotherapy. After 3 cycles the patient experienced disease hyperprogression for onset of a new lung mass, which resulted in squamous cell carcinoma. The preservation of an atypical mutation in the v-raf murine sarcoma viral oncogene homolog B1 (BRAF) gene in both the primary adenocarcinoma and the new squamous carcinoma suggests histological transformation, likely ICI-related. Discussion: We reviewed similar cases in literature, highlighting common patterns and substantial differences. For a deeper insight into inherent biological mechanisms, re-biopsy in case of atypical ICI response should be encouraged.